PENGARUH INTENSI TURNOVER DAN KETIDAKHADIRAN TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN DKI JAKARTA - Mutiara Annisa Fitri (Jurnal Manajemen Pendidikan, 2018)
The research was conducted to teachers education office of DKI Jakarta. By using a survey method with path analysis applied in testing hypothesis the number 52 employee as sample was selected by using Slovin formula. Based on the results of data analysis in this research it is concluded: (1) the turnover intention have negative direct effect to job performance; (2) the absenteeism have negative direct effect to job performance; (3) the turnover intention have positif direct effect to absenteeism.The job performance can be improved through reduction of turnover intention and absenteeism